Comparative Evaluation of Three Fecal Examination Methods for Detecting Gastrointestinal Parasites in Captive Macaca fascicularis (Indonesian Journal of Primatology, 2026)
Effective health monitoring of captive Macaca fascicularis requires reliable, sensitive diagnostic tools to detect gastrointestinal parasites. This study compared the diagnostic performance of three fecal examination methods, concentration-sedimentation, concentration-flotation, and the Kato-Katz technique, applied in parallel to fecal samples from 14 captive M. fascicularis at the Research Animal Facility Lodaya, Primate Research Center (PRC), IPB University, collected from October to December 2024. Concentration-sedimentation detected parasites in 78.6% of individuals (up to two parasite types per individual). The Kato-Katz method detected a single parasite type in 42.9% of individuals, while concentration-flotation yielded no positive results. Only protozoan parasites were identified: Entamoeba sp. and Balantidium coli. The detection of B. coli by the Kato-Katz method, theoretically unsuited for protozoan cysts, is attributed to its unusually large, thick-walled cysts. No helminth infections were found. These results confirm concentration-sedimentation as the most sensitive and appropriate routine diagnostic method for gastrointestinal parasite screening in captive macaques at this facility.